A Survey of Wireless Sensor Network Routing Protocols based on SPIN (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
SPIN(Sensor Protocols for Information via Negotiation) comprises of a set of adaptive protocols that proficiently disseminate data in wireless sensor network(WSN).SPIN overcomes certain deficiencies associated with some of the data dissemination protocols & brings in more efficiency. WSNs have limited energy and hence efficiency of protocol has a significant impact on network‟s lifetime. Many protocols have been developed that are based on SPIN and are its modifications. This paper presents a survey on SPIN protocol and the various protocols devised which use SPIN as a base in one or another way.